Temuan radiologi dalam kelainan kongenital atresia jejunum: serial kasus - Listyani Gunawan; Pande Putu Yuli Anandasari; Putu Patriawan (DiscoverSys Inc., 2021)
Background: Jejunoileal atresia is an emergency due to mechanical gastrointestinal obstruction, a rare case with a prevalence rate of 1-3 per 10,000 births. There is no difference in incidence by gender. Delay in treatment results in huge losses in terms of malnutrition, failure to thrive, and even death. These case series aim to evaluate radiological findings in congenital jejunal atresia.Case Presentation: There were 3 patients with the main complaint of bilious vomiting. These three patients underwent a plain abdominal x-ray examination, obtained a picture of a high total obstruction with a triple bubble picture, or had a dilated picture of the proximal obstruction. Partial obstruction based on plain radiographs in one of the patients was found, followed by an examination of contrast meal which filled smoothly up to the jejunum segment with a windsock appearance. The three cases have been proven through surgery, various types of jejunal atresia were obtained. Intestinal resection was performed, followed by an end-to-end jejunal anastomosis.Conclusion: Correct diagnosis determines the appropriate treatment for the patient. Plain abdominal radiograph as an initial examination in assessing total or partial obstruction in the jejunum, with a typical triple bubble or dilated bowel segment proximal to the obstruction. The windsock appearance of the jejunal segment on the contrast meal confirms the diagnosis of the jejunal web. Latar Belakang: Atresia jejunoileal merupakan kegawatdaruratan akibat obstruksi mekanik gastrointestinal, yang merupakan kasus jarang dengan angka prevalensi 1-3 per 10000 kelahiran, tidak ada perbedaan insiden berdasarkan gender. Terlambatnya tatalaksana mengakibatkan kerugian yang besar baik malnutrisi, gagal tumbuh, hingga kematian. Laporan kasus ini bertujuan untuk mengevaluasi temuan radiologi dalam kelainan kongenital atresia jejunum.Laporan Kasus: Terdapat 3 pasien dengan keluhan utama muntah bilosa. Kemudian dari pemeriksaan foto polos abdomen didapatkan gambaran obstruksi total letak tinggi dengan gambaran triple bubble atau memiliki gambaran dilatasi dari proksimal obstruksi. Obstruksi parsial berdasarkan foto polos pada salah satu pasien, dilanjutkan pemeriksaan contrast meal yang mengisi lancar hingga segmen jejunum dengan windsock appearance. Ketiga kasus tersebut telah terbukti melalui hasil operasi, didapatkan atresia jejunum berbagai tipe. Dilakukan reseksi usus dilanjutkan anastomosis end-to-end jejunal.Kesimpulan: Diagnosis yang tepat, menentukan tatalaksana yang sesuai bagi pasien. Foto polos abdomen sebagai pemeriksaan inisial dalam menilai obstruksi total atau parsial pada jejunum, dengan gambaran khas triple bubble atau dilatasi segmen usus proksimal dari obstruksi. Windsock appearance segmen jejunum pada contrast meal mempertajam diagnosis jejunal web.